Nightmares, chronotype, urbanicity, and personality: an online study - Schredl, Michael; Göritz, Anja (Clocks & sleep, 2020)
Chronotype refers to individual differences in sleep timing (“owls” and “larks”) and “eveningness” has been associated with nightmares. However, it has not been tested as to whether neuroticism mediates this relationship. Urbanicity refers to being raised in an urban region and/or currently living in an urban region and is associated with heightened risk for developing mental disorders, and thus might be related to nightmare frequency and nightmare distress. Overall, 2492 persons (1437 women, 1055 men) completed an online survey between 23 March 2015 and 8 April 2015. The mean age of the sample was 47.75 ± 14.41 years. The findings indicate that the previously reported relationship between chronotype and nightmare frequency was mediated by neuroticism and “morningness” was related to higher dream recall compared to persons with a late bedtime preference. Urbanicity was not related to nightmare frequency but to lower nightmare distress, raising the interesting question as to whether beliefs about nightmares might be an important variable that contributes to nightmare distress. Based on the few studies so far, there are still many unresolved questions about the interaction between nightmares, chronotype, and urbanicity.
Gesehen am 11.11.2025